Predictors of clinically meaningful change in PDQ-39 in Parkinson's disease. (November 2018) - Margolius, Adam; Cubillos, Fernando; He, Ying; Wu, Samuel; Schmidt, Peter; Simuni, Tanya; ,
Abstract: Objective: To determine predictors of clinically meaningful change in Health-Related Quality of Life (HRQL) in patients with Parkinson's disease (PD). Background: There is limited literature on longitudinal predictors of change in HRQL in PD. Methods: Data were collected from the National Parkinson Foundation Quality Improvement Initiative (NPF-QII) registry, a multicenter, longitudinal observational study. HRQL is measured by the Parkinson's Disease Questionnaire–39 (PDQ-39). We calculated the PDQ-39 change between every two consecutive visits and generated binary outcomes using the threshold for clinically meaningful change (previously determined to be 1.6). We used chi-squared tests for discrete and t -test for continuous variables for baseline characteristic comparison between patient groups of interest. Generalized linear mixed models with repeated measures were used for identifying the predictors of whether PDQ-39 outcomes worsen over time. Results: Of 8041 subjects enrolled, 5250 had at least one follow-up visit and were included in the analysis. Subjects were separated into two groups, "worse" and "not worse" based on PDQ-39 change >1.6 across consecutive visits. The "worse" group was more likely to be older (p = 0.001), to have motor fluctuations (p = 0.011), be on cognitive enhancers (p = 0.01), and to have more impaired immediate five-word recall (p = 0.04). The "non-worse" group was more likely to have rest tremor (p = 0.003), and to utilize social work/counseling (p = 0.046). Conclusions: The majority of predictors of worsening of HRQL are baseline disease and demographic characteristics that are difficult to modify. The positive effect of social service/counseling is intriguing and important to further explore in controlled interventional studies. Highlights: There is limited literature on longitudinal predictors of HRQL in Parkinson's disease. Most factors which are associated with worsening HRQL are difficult to modify. Subjects who use social services/counseling are less likely to have worsening of HRQL.